Reproductive Hormone Performance: Glass Strain Common carp (Cyprinus carpio) Reared in The Wet and Dry Seasons - Wati, Nadia Dara Panggita; Widodo, Maheno Sri; Hariati, Anik Martinah (International Journal of Marine Engineering Innovation and Research, 2025)
Glass strain carp (Cyprinus carpio) is highly demanded by farmers due to its delicious, dense meat and fewer spines. To meet the increasing demand for carp, it is necessary to improve the efficiency of aquaculture. The season is known to stimulate one hormone production. The purpose of this study was to determine the effect of season (rainy and dry seasons) on reproductive hormones (follicle stimulating hormone (FSH), luteinizing hormone (LH), testosterone and estrogen, and interstitial cell-stimulating hormone)) in C. carpio glass strain. Idi research was conducted using the descriptive method by rearing fish in different seasons (rainy season and dry season). The results showed that the reproductive hormone of C. carpio strain glass increased during the rainy season. During the rainy season, changes in the environment and water flow patterns are detected by the fish's sensory system. The results showed that the highest hormones in a row were: ICSH hormone (12.82 pg/mL), FSH hormone (male: 3.73 ng/mL; female: 12.10 ng/mL), LH hormone (12.48 MIU/ml), testosterone hormone (9.27 ng/mL) and estrogen hormone (21.84 ng/mL). Further research is needed to observe the growth and abnormality of fish larvae produced in different seasons.